Livestock in the food debate - Mehta-Bhatt, Purvi; Ficarelli, P.P. (Oxford University Press, 2014)
This chapter is from the forthcoming Oxford Handbook of Food, Politics, and Society edited by Ronald Herring. Livestock is an integral part of agriculture and a prominent source of food. It contributes 40% of the global value of agricultural output and supports the livelihoods and food security of almost a billion people, especially in developing countries. There is nothing new in amalgamation of farm animals in agriculture system, but the debate questioning its existence and relevance is a rather new drift. The politics, the climate debate, the nutrition debate around livestock sector, especially levitating from industrial countries, needs to be sympathetic toward the millions of people, especially in developing countries, that continue to remain dependent on livestock as an important, or often the only, source of livelihood. This chapter looks at the diverse livestock agriculture systems in industrial and less developed countries and it’s policy implications. It re-examines the prevailing debates such as, the heat and meat debate, the zoonotic disease discussions, the debate on ethics around animal-source food and the debate of over- and undernutrition. The authors take a balanced view on the pros and cons of livestock sector, considering the global debates, but at the same time, looking at livestock sector’s socioeconomic and nutrition value for the poor. Take a global view, debate, campaign but don’t forget to also look at the sector from livelihood and food-security angle. The underline message of the chapter is to call for a bounteous outlook, evidence-based debate and equable policies.